COVID-19 PANDEMIC AND THE DIALECTICS OF CULTURE - ONUAGHA, Amaka Veronica (Socialscientia: Journal of Social Sciences and Humanities, 2021)
The COVID-19 pandemic has impacted all human endeavours, namely, politics, education, culture, and economy globally. Nigeria is not exempted from the ramifying impact of the pandemic. Therefore, this article analyses the impact of COVID-19 on the way of life of selected communities in the Anambra State of Nigeria, traversing marriage institutions, family life, education, religion, and festivities. The article argues that the pandemic has greatly affected the studied communities, that is, Abatete, Ogidi, Uke, and Umuoji towns in the Idemili North local government area of Anambra. For example, traditional ceremonies like the Uzo-Iyi festival of Uke town, Uzo-Iyi of Umuoji town, Omaliko festival of Abatete town, Nwafor festival of Ogidi, and the Imo-Awka did not hold. While the article underlines the absence of conviction on the part of the studied population concerning the existence of COVID-19, it suggests the need for stakeholders to devise ways to educate the people on the necessity of adhering to the precautionary measures introduced by the government and its agencies. Equally, stakeholders should emphasize the point that observance of the rules and regulations governing COVID-19 by the people will not in any way jeopardize their cultures but rather enhance the wellbeing of the people.